2017
DOI: 10.1111/ggi.13029
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional study of equol producer status and cognitive impairment in older adults

Abstract: Compared with equol non-producers, equol producers showed an apparent beneficial effect in cognitive function after soy intake. Geriatr Gerontol Int 2017; 17: 2103-2108.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…In agreement with the previous literature, 28.7% of our study cohort were equol producers [38][39][40]. Limited evidence suggests that the ability to produce equol may confer beneficial effects on cognitive function following soy intake [66,67], potentially via increased cerebral blood flow [68]. We did not observe any significant differences in cognitive performance following intervention between equol producers and non-producers, although, within the high-dose group, improvements in spatial working memory in producers versus non-producers were approaching significance.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with the previous literature, 28.7% of our study cohort were equol producers [38][39][40]. Limited evidence suggests that the ability to produce equol may confer beneficial effects on cognitive function following soy intake [66,67], potentially via increased cerebral blood flow [68]. We did not observe any significant differences in cognitive performance following intervention between equol producers and non-producers, although, within the high-dose group, improvements in spatial working memory in producers versus non-producers were approaching significance.…”
Section: Discussionsupporting
confidence: 92%
“…A recent cross-sectional study of 152 elderly in Japan reported that S-equol-producers had significantly higher cognitive score (total dementia assessment score: 14.7 ± 0.7 vs. 14.3 ± 0.8, respectively, p=0.02) and lower prevalence of mild cognitive impairment (MCI) than non-producers (8% vs . 21%, respectively, p=0.04) [ 224 ]. In their multivariable-adjusted analysis, S-equol producing status had a significant association with both the cognitive score and presence of MCI.…”
Section: Brainmentioning
confidence: 99%
“…Very few observational studies have reported the association of S-equol with CHD [ 7 ] and cognitive impairment/dementia [ 224 ] or atherosclerosis/arterial stiffness [ 8 , 83 , 138 ], where most of studies are cross sectional. Soy isoflavones are regularly consumed only in some Asian countries.…”
Section: Future Directions Of Epidemiological and Clinical Research Omentioning
confidence: 99%
“…Equol, a metabolite of soy isoflavone, reflects the consumption of isoflavones. Igase et al (28) conducted a cross-sectional study on the association between equol production status and cognitive function in older adults. In contrast with equol producers, equol non-producers were more susceptible to cognitive decline.…”
Section: Flavonoids In Soy and Soy-derived Productsmentioning
confidence: 99%